Correlation between the Inner Canthal Distance and the Upper Central Incisor Mesiodistal Width Using the Decreasing Function of the Golden Ratio - Kajal Hayat, Hanzala Waqar, Yasir Hussain, Shahwar Ahmad, Muhammad Salman Khan, Zaheer Babar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Optimal aesthetics without sacrificing function is one of the main goals of prosthodontists. The face is the most noticeable aspect of the body, and a grin significantly increases one's sense of self-worth. Since aesthetics and subsequently self-esteem are both impacted by the loss of anterior teeth, this frequently causes psychological anguish for the patient. The quality of life and self-esteem of patients are improved by the proper tooth location and choice employing the art of dentogenics to simulate real teeth. Aim: To determine whether there is a relationship between the average mesiodistal width of the upper central incisor and the inner canthal distance when the ICD is multiplied by the decreasing golden ratio, as well as to evaluate the significance of this relationship in predicting mesiodistal width of the upper central incisor in subjects with edentate disease. Methodology: This cross-sectional study was carried out at Department of Prosthodontics, Bacha Khan College of Dentistry Mardan from October 2022 to March 2023. Four hundred and fifty dentate Pakistani subjects without dental or facial abnormalities, aged 18 to 40, were examined. With the use of veriner callipers, the central upper incisors were noted mesiodistally amongst the interproximal contact sites and inner canthal space. The inner canthal space was multiplied by 0.618, and the width of the central incisor was calculated by dividing the result by 2. Results: Statistically significant finding demonstrated with inner canthal distance was exposed to the golden ratio. There was only a modest link among the practical mesiodistal width of the central upper incisors and the estimated central upper incisor width. Conclusion: For edentulous patients, choosing the width of the upper central incisors using the decreasing value of the inner canthal distance's golden ratio was not a valid predictor. Keywords: Edentulous, Golden ratio, Inner canthal distance (ICD)